2017
DOI: 10.1051/matecconf/201710306003
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Vetiver Grass (Vetiveria zizanioides) for Phytoremediation of Contaminated Water

Abstract: Abstract. In tolerance towards metal uptake, there is a need to evaluate the performance of vetiver grass for metal removal to reduce water impurity. This study was aimed to evaluate contaminant removal by vetiver grass at varying root length and plant density and determine the metal uptake in vetiver plant biomass. Pollutant uptake of vetiver grass was conducted in laboratory experiment and heavy metal analysis was done using acid digestion and Atomic Absorption Spectrometry. Findings indicated that the remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 12 publications
0
3
0
2
Order By: Relevance
“…The potential of vetiver grass in wastewater treatment was analysed by Maharajan and his team [26] and the results of the study showed that treating of waste water by vetiver grass can reduce the overall concentration of chloride nitrate total hardness and alkalinity by 42.90%, 93.93%, 46.4% and 22.2% respectively. It can also lower the parameters such as chloride, sulphate, calcium; magnesium and iron [26][27][28]. This could be the reason for the drastic change in the parameters of water after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The potential of vetiver grass in wastewater treatment was analysed by Maharajan and his team [26] and the results of the study showed that treating of waste water by vetiver grass can reduce the overall concentration of chloride nitrate total hardness and alkalinity by 42.90%, 93.93%, 46.4% and 22.2% respectively. It can also lower the parameters such as chloride, sulphate, calcium; magnesium and iron [26][27][28]. This could be the reason for the drastic change in the parameters of water after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This manifested that Cr and Cu are generally retained in the roots. Metal uptake was higher in the root than in the leaf due to the plant root structure, which can form a high surface area and restrict heavy metal translocation from root to leaf [4,12].…”
Section: Microbial-assisted Phytoremediation Potential Of Vetiver (Ch...mentioning
confidence: 99%
“…The threshold levels of C. zizanioides are 5-18 mg kg -1 and 13-15 mg kg -1 of Cr and Cu respectively, while for other plants are 0.02-0.20mg kg -1 and 15 mg kg -1 . It involves a translocation process of the contaminants uptake by plants roots which act as phytoextraction [12].…”
Section: Introductionmentioning
confidence: 99%
“…Verskeie outeurs, waaronder Truong & Creighton (1994), Truong (2002), en Vargas et al, (2016) het aangetoon dat C. zizanioides relatiewe hoë konsentrasies van swaarmetale soos chroom (Cr), koper (Cu), lood (Pb), kwik (Hg), nikkel (Ni), mangaan (Mn), sink (Zn) en yster (Fe), asook elemente soos arseen (As) in die blare en wortels kan akkumuleer. Roongtanakiat et al, (2007), Chen et al, (2011) en Hasan et al, (2017) het C. zizanioides aan oppervlakwater wat met verskillende konsentrasies metale gekontamineer was, blootgestel om vas te stel watter metale die plant effektief kan opneem. Hieruit was dit duidelik dat die oorgrote meerderheid van die metale in die wortels akkumuleer en dat veral Pb, Fe, Mn and Zn in relatiewe hoë konsentrasies in die wortels teenwoordig was (Hasan et al, 2017;Antiochia et al, 2007;Roongtanakiat et al, 2007).…”
unclassified
“…Roongtanakiat et al, (2007), Chen et al, (2011) en Hasan et al, (2017) het C. zizanioides aan oppervlakwater wat met verskillende konsentrasies metale gekontamineer was, blootgestel om vas te stel watter metale die plant effektief kan opneem. Hieruit was dit duidelik dat die oorgrote meerderheid van die metale in die wortels akkumuleer en dat veral Pb, Fe, Mn and Zn in relatiewe hoë konsentrasies in die wortels teenwoordig was (Hasan et al, 2017;Antiochia et al, 2007;Roongtanakiat et al, 2007).…”
unclassified